2011
DOI: 10.1007/s11664-011-1509-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Thermoelectric Properties of Dense YB22C2N Samples Fabricated Through Spark Plasma Sintering

Abstract: Dense samples of the higher boride YB 22 C 2 N have been fabricated through the spark plasma sintering (SPS) method with different sintering aids. YB 22 C 2 N is a representative of a series of newly discovered rare-earth borocarbonitrides, which may be the long-awaited n-type counterpart of boron carbide, ''B 4 C.'' The effect of Si, SiC, Al, and TiC additions on the sintering process of YB 22 C 2 N has been studied. The best sintered bodies with densities higher than 90% of theoretical density were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Incidentally with SPS it was previously found that the densities could be increased to ∼75% with spark plasma sintering (SPS) 33 or further to even 95% with additives in SPS. 35,38 For simply cold pressed "pure" Y 1−x B 28.5 C 4 the achieved density was a little higher than the "conventional" case and reached ∼65%.…”
Section: Methodsmentioning
confidence: 88%
“…Incidentally with SPS it was previously found that the densities could be increased to ∼75% with spark plasma sintering (SPS) 33 or further to even 95% with additives in SPS. 35,38 For simply cold pressed "pure" Y 1−x B 28.5 C 4 the achieved density was a little higher than the "conventional" case and reached ∼65%.…”
Section: Methodsmentioning
confidence: 88%
“…Titanium diboride (TiB 2 ) is compatible with B 4 C because B 4 C and TiB 2 form binary eutectic composites. Therefore, the TiB 2 phase would be suitable to improve the electrical and thermal conductivity of B 4 C. The electrical conductivity of the B 4 C-TiB 2 composites significantly increased with increasing TiB 2 content, [40][41][42][43][44][45][46] which will enable the potential use of composites as thermoelectrics in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The compositions' behavior was evaluated. The samples were subjected to isostatic pressing [41][42][43] before sintering to improve the composite properties. This study describes the free sintering and reactive sintering of hot-pressed composites based on commercial boron carbide with boron and titanium additives.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth borocarbonitrides, RB 22 C 2 N, RB 17 CN and RB 28.5 C 4 , were discovered to be the first boron icosahedra cluster containing compounds that exhibit intrinsic n-type thermoelectric materials [14,15]. Some of the recently discovered novel borides have been found not to be easy to obtain dense samples, and various studies to remedy this have been carried out; for example, mechanical grinding and sintering the sample through the spark plasma sintering (SPS) treatment with sintering aids such as metals, rare earth tetra brides and carbides [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%